A Full Vacuum Approach for the Fabrication of Hybrid White‐Light‐Emitting Thin Films and Wide‐Range In Situ Tunable Luminescent Microcavities. Issue 7 (19th April 2016) - Oulad‐Zian, Youssef; Sanchez‐Valencia, Juan Ramon; Oliva, Manuel; Parra‐Barranco, Julian; Alcaire, Maria; Aparicio, Francisco J.; Mora‐Boza, Ana; Espinos, Juan Pedro; Yubero, Francisco; Gonzalez‐Elipe, Agustin R.; Barranco, Angel; Borras, Ana
Abstract : This study shows the fabrication by a dry approach at mild temperature (<150 °C) of a photoluminescence white light emitting hybrid layer. The white light emitter is obtained by evaporation of two photoluminescent small molecules, a blue (1, 3, 5‐triphenyl‐2‐pyrazoline (TPP)) and an orange (Rubrene) dye within the porous of an SiO2 host film fabricated by glancing angle deposition. Fluorescence (Föster) resonant energy transfer between the two organic dyes allows the emission of the combined system upon excitation of the TPP molecule at wavelength of 365 nm. The distribution of the organic molecule within the host layer is analyzed as a function of the substrate temperature and vacuum conditions and the required conditions for the white emission determined by finely controlling the TPP:Rubrene ratio. The full vacuum processing of the hybrid layers provides a straightforward route for the incorporation of the white light emitters as optical defect within 1D Bragg microcavities. As a consequence, directional emission of the system is achieved which allows the development of wide‐range in situ tunable photoluminescent devices. Abstract : In this study, photoluminescence white‐light‐emitting hybrid layers are fabricated by a full vacuum approach at low temperatures. White emission is obtained by fluorescence (Förster) resonant energy transfer between a blue (1, 3, 5‐triphenyl‐2‐pyrazoline) and an orange (Rubrene) dye within an SiO2 host film formed by glancing angle deposition (GLAD). Directional luminescent emitters and wide‐range in situ tunable devices are developed by further integration within 1D Bragg microcavities.